The effect of product innovation strategies on sales growth of a firm: a case study of ecobank ghana plc. - ASAMOAH MAVIS AWUKU (KNUST, 2024)
This thesis is submitted to the department of marketing in partial fulfilment of the requirement for the award of master of science in marketing